2000
DOI: 10.1080/07408170008967441
|View full text |Cite
|
Sign up to set email alerts
|

Risk intermediation in supply chains

Abstract: This paper demonstrates that an important role of intermediaries in supply chains is to reduce the ®nancial risk faced by retailers. It is well known that risk averse retailers when faced by the classical single-period inventory (newsvendor) problem will order less than the expected value maximizing (newsboy) quantity. We show that in such situations a risk neutral distributor can oer a menu of mutually bene®cial contracts to the retailers. We show that a menu can be designed to simultaneously: (i) induce ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 20 publications
1
102
2
2
Order By: Relevance
“…Therefore, risk aversion of the retailers has been portrayed in the literature as leading to the loss of efficiency in 23 supply chains. Agrawal and Seshadri (2000) showed not only that this loss 25 of efficiency can be eliminated through risk reducing pricing contracts, but also that any risk neutral intermediary will find it 27 beneficial to offer such risk reducing contracts to the retailers. In their model, the intermediary is referred to as the distributor 1 29 who purchases the goods as per the terms of the ONC from the vendor, and in turn offers the goods to the retailers on contract 31 terms that are less risky from the retailers' viewpoint.…”
Section: Demand Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, risk aversion of the retailers has been portrayed in the literature as leading to the loss of efficiency in 23 supply chains. Agrawal and Seshadri (2000) showed not only that this loss 25 of efficiency can be eliminated through risk reducing pricing contracts, but also that any risk neutral intermediary will find it 27 beneficial to offer such risk reducing contracts to the retailers. In their model, the intermediary is referred to as the distributor 1 29 who purchases the goods as per the terms of the ONC from the vendor, and in turn offers the goods to the retailers on contract 31 terms that are less risky from the retailers' viewpoint.…”
Section: Demand Riskmentioning
confidence: 99%
“…Standard analysis shows that the optimal order quantity under the ONC 27 is given by the "fractile rule" which depends on both the demand distribution as well as the retailer's utility function. 29 Agrawal and Seshadri (2000) showed that, if retailers have different risk preferences, the single contract offered by the 31 vendor may not achieve the optimal risk reduction. Thus, in practice risk intermediation is often employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moorthy (1987) argued that a two-part tariff can motivate the retailer to set the channelprofit maximizing price in a decentralized channel. Agrawal and Seshadri (2000) considered a two-part tariff contract that coordinates a risk-averse retailer and a risk-neutral distributor. A two-part tariff can not only increase order quantity of the retailers to the optimal level, but also maximize the distributor's expected profit.…”
Section: Relation To Literaturementioning
confidence: 99%
“…Implications for setting returns contracts for achieving channel coordination with risk considerations are discussed. Some other recent research works which analyse the risk issues in supply chain management include a qualitative discussion on proactive supply management and its close relationship with risk management (Smeltzer & Siferd 1998), a quantitative analysis of the role of intermediaries in supply chains to reduce financial risk (Agrawal & Seshadri 2000), a mean-variance analysis of single echelon inventory problems (Chen & Federgruen 2000), a study of the risk-free perishable item returns policy with a risk neutral retailer in a two-echelon supply chain (Webster & Weng 2000), an investigation of the use of capacity options in managing risk www.intechopen.com from demand uncertainty (Tan 2002), an analysis of the use of commitment-option for supply chain contract setting with forecast updates (Buzacott et al 2003), a study on contracting scheme with risk preferences considerations (Bassok & Nagarajan 2004), a meanvariance analysis for the newsvendor problem with and without the opportunity cost of stock out (Choi et al 2007a), and a study on channel coordination in supply chains under mean-variance objectives (Choi et al 2007b) …”
Section: Literature Reviewmentioning
confidence: 99%